Potential photosensitizer candidates for PDT including 7-oxy-3-thiomethylphenyl coumarino-phthalocyanines - (:unkn) unknown (ELSEVIER SCIENCE SA, 2019)
In this work, the novel phthalonitrile derivatives and their peripheral/nonperipheral phthalocyanine analogues including 7-oxy-3-(p-thiomethylphenyl) coumarin were synthesized and purified. All these novel compounds were characterized by common characterization methods such as FT-IR, UV-vis, MALDI-TOF, 1H-NMR and elemental analysis. Furthermore, the photochemical and photophysical properties of newly synthesized zinc(II) and indium(III) phthalocyanines were investigated in N,N-dimethylformamide (DMF) solutions. The substituent effect toward the phthalocyanine center and the metal effect on the photophysicochemical properties were also investigated.
Keywords: Phthalocyanine; Coumarin; Singlet oxygen; PHOTOCHEMICAL PROPERTIES; DERIVATIVES; RED